Prospects for Developing Digital-Based Tourist Attractions Through Songko Recca as Content Marketing - Haedar, Ahmad Wahidiyat (PINISI Discretion Review, 2025)
The prospect of developing digital marketing-based tourist attractions is a serious effort to promote regional tourism potential through digital platforms such as social media, websites, applications, and search engines. In this digital era, the use of internet-based marketing strategies allows for the dissemination of information quickly, efficiently, and more widely to diverse target markets. This method includes online campaigns, internet marketing, and the use of data to adjust promotional content according to the interests and needs of tourists. This research article explains the prospects for developing digital marketing-based tourist attractions through Songko Recca as digital content. Data were obtained through observation, interviews and documentation to be analyzed using an interactive model that includes data collection, data condensation, data presentation, and verification/drawing conclusions. The results of the study indicate that the development of digital marketing-based tourist attractions through Songko Recca is very prospective because Songko Recca is an Icon of Bone Regency. Songko` Recca or Songko To Bone also known as Songkok Bugis is one of the cultural works of the Bone community. Songko` Recca has officially become an intangible cultural heritage of Indonesia based on the determination of the Indonesian Ministry of Education and Culture in 2018.